2016
DOI: 10.1042/bcj20160846
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the plant molybdenum insertase Cnx1E is required for synthesis of the molybdenum cofactor

Abstract: The molybdenum cofactor (Moco) is a redox active prosthetic group, essentially required for numerous enzyme-catalyzed two electron transfer reactions. Moco is synthesized by an evolutionarily old and highly conserved multistep pathway. In the last step of Moco biosynthesis, the molybdenum center is inserted into the final Moco precursor adenylated molybdopterin (MPT-AMP). This unique and yet poorly characterized maturation reaction finally yields physiologically active Moco. In the model plant Arabidopsis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(85 citation statements)
references
References 57 publications
6
79
0
Order By: Relevance
“…Within the Cnx1E active site, MPT-AMP adopts a conformation that is different from the one found in the Cnx1G MPT-AMP co-structure [11] and that properly orients the dithiolene motif toward enzyme bound molybdate [14,15]. Subsequently the MPT-AMP phosphoric anhydride bond is hydrolyzed, a reaction that is believed to be the prerequisite for enzyme catalyzed molybdate insertion into the MPT dithiolene motif [13][14][15]. Recent work suggested that the Cnx1E catalyzed molybdate insertion reaction involves the relocation of molybdate from the initial oxo-anion binding site to the insertion site [15].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…Within the Cnx1E active site, MPT-AMP adopts a conformation that is different from the one found in the Cnx1G MPT-AMP co-structure [11] and that properly orients the dithiolene motif toward enzyme bound molybdate [14,15]. Subsequently the MPT-AMP phosphoric anhydride bond is hydrolyzed, a reaction that is believed to be the prerequisite for enzyme catalyzed molybdate insertion into the MPT dithiolene motif [13][14][15]. Recent work suggested that the Cnx1E catalyzed molybdate insertion reaction involves the relocation of molybdate from the initial oxo-anion binding site to the insertion site [15].…”
Section: Introductionmentioning
confidence: 86%
“…Cnx1E variant D274E was generated following the QuikChange (Agilent Technologies) protocol modified for the use of Phusion ® High-Fidelity DNA Polymerase (Thermo Fischer). As described earlier [15], we used the Cnx1E wild-type pGPlus expression vector [14] as template for PCR-based mutagenesis. The sequence of the primer pair used to introduce the single amino acid exchange D274E was 5´-gggagacagggaGttcgtcaagccattactcgaag-3´and 5´-agtaatggcttgacgaaCtccctgtctcccattga-3´(mismatches in upper case).…”
Section: Generation Of Cnx1e Variant D274ementioning
confidence: 99%
See 2 more Smart Citations
“…[1] Next to Moco/MPT quantification of recombinant Moco dependent enzymes, [2,3] quantification of dephospho Form A( 4)h as also become of key importance for the determinationo ft he Moco/MPT content also of thoseproteins that are involved in the biosynthesis of Moco. [4,5] The detection limit of 4 by HPLC/fluorescence spectroscopy is in the picomolarr ange, which makes that quantification protocol suitable forb oth recombinant biochemistry andf or the characterization of biological samples, for example mutants trains. [6,7] The procedure was first reported by Rajagopalan and co-workers, [8] and modified later.…”
Section: Introductionmentioning
confidence: 99%